ADULT T-CELL LEUKEMIA / LYMPHOMA COMPLICATED WITH SAPROCHAETE CAPITATA FUNGEMIA – CASE REPORT - Sotirova, Tatjana; Karanfilski, Oliver; Genadieva Stavrikj, Sonja; Pavkovikj, Marica; Krstevska Balkanov, Svetlana (Turkish Society of Hematology, 2015)
Adult T cell leukemia/lymphoma (ATLL) is a rare and often aggressive T - lymphoproliferative disorder, etiologically linked with human T cell lymphotropic virus type-1 (HTLV-1). HTLV-1 is endemic in Japan, Caribbean and Africa, although sporadic cases have been reported elsewhere in the world. ATLL affects almost exclusively adults. There is no gender prevalence. Depending on the disease manifestations, ATLL is classified into several forms: acute, chronic or smoldering. Treatment of ATLL remains a challenge for the clinicians Patients with ATLL are immunocompromised and develop opportunistic infections that complicate the disease course and make its management even more difficult. Infection with Saprochaete capitata has been reported in patients with hematological malignancies, especially in acute leukaemia. But, so far, infection with Saprochaete capitata in the ATLL patients has not been reported. We report a case of a 54 year old woman presented at the University Clinic of Hematology in Skopje, Macedonia, in July 2014, with intensive itching, coughing, dyspnea and skin tumorous formations. Physical examination revealed neither peripheral adenopathy nor organomegaly. Diagnosis was made upon several investigations. Beside the presence of skin lesions she had elevated white blood cells (55,9 X 109 /L) with atypical lymphomonocytoid cells. The bone marrow (BM) smear showed 80-90% lymphoid infiltration. The histopathological finding was - Malignant lymphoma. PCR of BM aspirate showed dominant monoclonal population of T lymphocytes. Immuno-phenotyping of bone marrow cells showed positivity for CD3, CD2, CD4, CD5, CD7, CD10, CD25, CD38 and negative FCM7, CD79b and CD22, confirming ATLL. Treatment started with CHOP protocol due to acute renal failure. In the course of the disease she complained she couldn’t walk. MRI of the back bone revealed vertebral sclerosis with spinal stenosis L4-L5. After 3 cycles, treatment continued with Hyper-C-VAD regimen. After the first cycle, she became neutropenic and febrile. Microbiological finding was Saprochaete capitata. Despite treatment, she succumbed to her illness five days from the beginning of the febrile episode and six months from the presentation due to Saprochaete capitata fungemia. Keywords: Adult T cell leukemia/lymphoma, Saprochaete capitata
Keywords: Adult T cell leukemia/lymphoma; Saprochaete capitata